Study on Hepatitis B and Hepatitis C in Haemodialysis patients of National Institute of Kidney Diseases and Urology (NIKDU), Dhaka (Bangladesh Journal of Medicine, 2015)
Hepatitis viral infections are important causes of morbidity and mortality in haemodialysis patients. The present study was undertaken to estimate the prevalence of HBV and HCV and dual infection among haemodialysis patients attending at National Institute of Kidney Diseases and Urology (NIKDU), Sher EBangla Nagar, Dhaka during the period between January 2012 to April 2013. One hundred and fifty patients attending haemodialysis unit were screened for the presence of HBV and HCV infections. 22 (14.67%) patients were HCV positive while 18 (12%) patients had HBV infection. A dual infection with both the viruses was observed in 1 patient (.67%).Bangladesh J Medicine Jul 2014; 25 (2) : 55-60